Sodium glucose cotransporter 2 inhibitors and risk of serious adverse events: nationwide register based cohort study. (14th November 2018) - Ueda, Peter; Svanström, Henrik; Melbye, Mads; Eliasson, Björn; Svensson, Ann-Marie; Franzén, Stefan; Gudbjörnsdottir, Soffia; Hveem, Kristian; Jonasson, Christian; Pasternak, Björn
Abstract: Objective: To assess the association between the use of sodium glucose cotransporter 2 (SGLT2) inhibitors and seven serious adverse events of current concern. Design: Register based cohort study. Setting: Sweden and Denmark from July 2013 to December 2016. Participants: A propensity score matched cohort of 17 213 new users of SGLT2 inhibitors (dapagliflozin, 61%; empagliflozin, 38%; canagliflozin, 1%) and 17 213 new users of the active comparator, glucagon-like peptide 1 (GLP1) receptor agonists. Main outcome measures: The primary outcomes were lower limb amputation, bone fracture, diabetic ketoacidosis, acute kidney injury, serious urinary tract infection, venous thromboembolism, and acute pancreatitis, as identified from hospital records. Hazard ratios and 95% confidence intervals were estimated by using Cox proportional hazards models. Results: Use of SGLT2 inhibitors, as compared with GLP1 receptor agonists, was associated with an increased risk of lower limb amputation (incidence rate 2.7 v 1.1 events per 1000 person years, hazard ratio 2.32, 95% confidence interval 1.37 to 3.91) and diabetic ketoacidosis (1.3 v 0.6, 2.14, 1.01 to 4.52) but not with bone fracture (15.4 v 13.9, 1.11, 0.93 to 1.33), acute kidney injury (2.3 v 3.2, 0.69, 0.45 to 1.05), serious urinary tract infection (5.4 v 6.0, 0.89, 0.67 to 1.19), venous thromboembolism (4.2 v 4.1, 0.99, 0.71 to 1.38) or acute pancreatitis (1.3 v 1.2, 1.16, 0.64 to 2.12). Conclusions: In this analysis of nationwide registers from two countries, use of SGLT2 inhibitors, as compared with GLP1 receptor agonists, was associated with an increased risk of lower limb amputation and diabetic ketoacidosis, but not with other serious adverse events of current concern.